A randomized controlled trial of web-based training to increase activity in children with cerebral palsy - Mitchell, L.; Ziviani, J.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2016)
Aim: To determine the efficacy of web-based training on activity capacity and performance in children with unilateral cerebral palsy (CP). Method: In a matched-pairs randomized waitlist controlled trial, independently ambulant children and adolescents with unilateral CP were allocated to receive 30 minutes of training (intervention) 6 days per week, or usual care (waitlist control) for 20 weeks. Activity capacity was assessed using maximal repetitions of functional strength tasks and 6-minute walk test (6MWT); performance using 4-day ActiGraph GT3X+ accelerometer records at baseline and 20 weeks. Data were analysed by intention to treat comparing between groups using hierarchical linear modelling. Results: Participants were n=101, 52 males, mean age 11 years 3 months (SD 2y 4mo). Intervention participants completed a mean 32.4 hours (SD 17.2) of training, associated with significant improvements in functional strength (mean difference 19.3 repetitions; 95% confidence interval [CI] 10.8–27.7; <0.001) and 6MWT distance (mean difference 38.9m; 95% CI 12.3–51.9; <0.001) compared with the control group at 20 weeks, although not activity performance (>0.05). Interpretation: Training was effective at increasing functional strength and walking endurance in independently ambulant children with unilateral CP. This did not translate into improvements in activity performance.